Genetic diversity among bovine racial subpopulations of Costa Rica - Martínez, Marco (2015)
Genetic diversity among bovine racial subpopulations of Costa Rica. The objetive of this study was to quantify the genetic diversity among 16 bovine racial subpopulations of Costa Rica, based on 1412 samples of bovine DNA from around the country, which were evaluated using 18 microsatellite markers. Average number of alleles (Na) per locus within breed was 10.3, ranging from 8 (Holstein×Jersey) to 13 (Dual Purpose Creole). Average number of effective alleles (Ne) was 5.04, ranging between 4.18 (Jersey) and 5.64, (Bos taurus×Bos indicus). Average observed heterocigozity (Ho) was 0.77, varying between 0.73 (Jersey) and 0.81 (Bos taurus×Bos indicus). Average expected heterocigozity (He) was 0.78, oscillating between 0.74 (Jersey and Holstein×Jersey) and 0.81 (Bos taurus×Bos indicus, dual purpose Creole and dual purpose Crosses). The polymorphic information content (PIC) was 0.76, ranging between 0.71 (Jersey and Holstein×Jersey) and 0.79 (dual purpose Creole and dual purpose crosses). Average FIS was 0.02, ranging from -0.03 (Holstein×Jersey) to 0.04 (Brahman, Beef Creole and Dairy crosses). Deviation from Hardy Weinberg equilibrium was not significant (p>0.05) for the majority of loci within racial subpopulations. Subgroup with the highest number of loci in disequilibrium was Jersey (8 loci), while subgroups Bos taurus×Bos indicus, Dairy Creole and Holstein×Jersey showed only 1 locus in disequilibrium. Fixation indexes FIS (0.02), FIT (0.05) and FST (0.03) indicated some tendency towards homocigozity. The dendrograms showed 3 distinct racial groups that match races of Bos taurus, origin Bos indicus and their crosses. The results of the analysis indicated that the number of microsatellites used allowed to establish a clear discrimination at the level of the alelic frequencies and in the distribution of the size of aleles between the subpopulations of different species and even between pure races.